2010
DOI: 10.1189/jlb.0509307
|View full text |Cite
|
Sign up to set email alerts
|

The role of interferon-γ in the pathogenesis of acute intra-abdominal sepsis

Abstract: Several studies indicate that IFN-γ facilitates systemic inflammation during endotoxin-induced shock. However, the pathobiology of IFN-γ in clinically relevant models of septic shock, such as CLP, is not well understood. In this study, the role of IFN-γ in the pathogenesis of CLP-induced septic shock was evaluated by examining IFN-γ production at the tissue and cellular levels. The impact of IFN-γ neutralization on systemic inflammation, bacterial clearance, and survival was also determined. Following CLP, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
4
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 39 publications
(44 reference statements)
2
40
4
3
Order By: Relevance
“…Serum cytokines were also assessed in the same mice to correlate the strength of the systemic inflammatory responses. Six hours after LPS challenge, cytokines characteristic of lethal endotoxicosis (32), such as IFN-γ, were decreased in mice deficient for IFNAR1 or IL-28R. The early TNF-α signal was significantly decreased in IFNAR1 −/− mice only whereas no differences were found in serum KC levels between WT and IL-28R…”
Section: Il-28r Deficiency Sensitizes Mice To Lps-induced Endotoxicosmentioning
confidence: 96%
See 1 more Smart Citation
“…Serum cytokines were also assessed in the same mice to correlate the strength of the systemic inflammatory responses. Six hours after LPS challenge, cytokines characteristic of lethal endotoxicosis (32), such as IFN-γ, were decreased in mice deficient for IFNAR1 or IL-28R. The early TNF-α signal was significantly decreased in IFNAR1 −/− mice only whereas no differences were found in serum KC levels between WT and IL-28R…”
Section: Il-28r Deficiency Sensitizes Mice To Lps-induced Endotoxicosmentioning
confidence: 96%
“…To address whether the absence of IFN-λ signaling also regulated systemic polymicrobial sepsis and septic shock, a cecal ligation and puncture (CLP) model was performed as previously described (33). Because lethality was shown to be dependent upon NK cell IFN-γ production (32,34,35), not surprisingly the IL-28R −/− mice were relatively resistant compared with WT mice (Fig. 3A).…”
Section: Il-28rmentioning
confidence: 99%
“…This deleterious effect was also shown in the CLP model of polymicrobial peritonitis (92) and in a CLP model followed by a P. aeruginosa infection (93). Polymicrobial peritonitis performed in IFN-γ receptor-deficient mice (94) or in rats given anti-IFN-γ antibodies (95) led to the similar demonstration of this negative role. In mice injected with LPS, the ambiguous role of IFN-γ was demonstrated: IFN-γ protected against LPSinduced lung edema but acted in synergy with LPS to enhance the occurrence of death (96).…”
Section: Nk Cells As a Source Of Inflammatory Cytokines And Antimicromentioning
confidence: 60%
“…Several studies have shown that the physiopathology observed in SOCS1-knockout mice depends on IFN-γ production (30)(31)(32). Additionally, IFN-γ plays a detrimental role in polymicrobial sepsis (33). Therefore, we evaluated whether pharmacological inhibition of SOCS1 would lead to elevated levels of IFN-γ.…”
Section: Resultsmentioning
confidence: 99%